Long-term social isolation stress exacerbates sex-specific neurodegeneration markers in a natural model of Alzheimer's disease - Oliva, Carolina A.; Lira, Matias; Jara, Claudia; Catenaccio, Alejandra; Mariqueo, Trinidad A.; Lindsay, Carolina B.; Bozinovic, Francisco; Cavieres, Grisel; Inestrosa, Nibaldo C.; Tapia-Rojas, Cheril; Rivera, Daniela S. (My University, 2023)
Social interactions have a significant impact on health in humans and animal models. Social isolation initiates a cascade of stress-related physiological disorders and stands as a significant risk factor for a wide spectrum of morbidity and mortality. Indeed, social isolation stress (SIS) is indicative of cognitive decline and risk to neurodegenerative conditions, including Alzheimer's disease (AD). This study aimed to evaluate the impact of chronic, long-term SIS on the propensity to develop hallmarks of AD in young degus (Octodon degus), a long-lived animal model that mimics sporadic AD naturally. We examined inflammatory factors, bioenergetic status, reactive oxygen species (ROS), oxidative stress, antioxidants, abnormal proteins, tau protein, and amyloid-beta (A beta) levels in the hippocampus of female and male degus that were socially isolated from post-natal and post-weaning until adulthood. Additionally, we explored the effect of re-socialization following chronic isolation on these protein profiles. Our results showed that SIS promotes a pro-inflammatory scenario more severe in males, a response that was partially mitigated by a period of re-socialization. In addition, ATP levels, ROS, and markers of oxidative stress are severely affected in female degus, where a period of re-socialization fails to restore them as it does in males. In females, these effects might be linked to antioxidant enzymes like catalase, which experience a decline across all SIS treatments without recovery during re-socialization. Although in males, a previous enzyme in antioxidant pathway diminishes in all treatments, catalase rebounds during re-socialization. Notably, males have less mature neurons after chronic isolation, whereas phosphorylated tau and all detectable forms of A beta increased in both sexes, persisting even post re-socialization. Collectively, these findings suggest that long-term SIS may render males more susceptible to inflammatory states, while females are predisposed to oxidative states. In both scenarios, the accumulation of tau and A beta proteins increase the individual susceptibility to early-onset neurodegenerative conditions such as AD.
Keywords: octodon degus; social isolation stress; amyloid-beta protein; tau protein; inflammation; oxidative stress